Peran Teknologi Informasi dalam Mendorong Internasionalisasi UMKM - Dayat, M. Dayat; Imam, Imam, Mukhlis; Fulgentius, Fulgentius Danardana Murwani (CV. Satria Jaya, 2024)
This study aims to examine the role of information technology in driving the internationalization of Micro, Small, and Medium Enterprises (MSMEs). Using a literature study approach, this study collects data from various sources such as scientific journals, books, reports, and relevant articles. Content analysis is used to identify the main themes, code the data, and interpret the results to find patterns and relationships between variables related to the research topic. The results of the study show that information technology plays an important role in various aspects of MSME internationalization, including digital marketing, supply chain management, and international payments. The challenges faced by MSMEs in adopting information technology include resource constraints, lack of technological knowledge, and cybersecurity issues. Effective strategies for utilizing information technology for internationalization include investing in technology training, collaborating with technology companies, and utilizing easily accessible and usable digital platforms. This study concludes that support from the government and related institutions is essential to strengthen the digital ecosystem that supports MSME internationalization